Allocating Attention to Detect Motorcycles: The Role of Inattentional Blindness. (February 2018) - Pammer, Kristen; Sabadas, Stephanie; Lentern, Stephanie
Objective: To determine whether inattentional blindness (IB) can be used to understand the psychological mechanisms around looked-but-failed-to-see (LBFTS) crashes involving motorcycles Background: IB occurs when an observer looks directly at an object yet fails to see it, thus LBFTS crashes may be a real-world example of IB. The study tests a perceptual cycle model in which motorcycles are detected less frequently because they fall lower on the attentional hierarchy for driving. Method: A driving-related IB task with photographs of driving situations investigated whether an additional stimulus, a taxi or motorcycle, would be more likely to be missed by participants. In Experiments 2 and 3, the "threat value" of objects in the scene were varied to determine the degree to which this influences participants' tendency to notice motorcycles. Results: Participants were twice as likely to miss a motorcycle compared with a taxi. Moreover, participants reported that they would expect to miss a motorcycle on the road. In Experiments 2 and 3, participants modulated their attention to accommodate motorcycles when necessary, suggesting that motorcycles are afforded the lowest level of attentional bandwidth. Conclusion: Inattentional blindness forms a good psychological framework for understanding LBFTS crashes, particularly in the context of attentional set, such that LBFTS crashes occur because motorcycles do not feature strongly in a typical driver's attentional set for driving. Application: The findings here are important because LBFTS crashes can be reduced if we can change the expectations of road users around the presence of motorcycles on the road.